The Role and Perception of Parents in Guiding Students’ Mathematics Learning During the Covid-19 Pandemic - Habibi, Mhmd; Erdayani, Rizki; Susanti, R. Hariyani; Mulfina, Emelya Putri; Qomariah, Winda Fajar; Ilham, Muhammad; Fitri, Intan (Tarbawi : Jurnal Ilmu Pendidikan, 2022)
The Covid-19 pandemic has compelled a shift to online learning, thereby necessitating parental involvement in their children's education at home. In this study, we aim to explore the perceptions and roles of parents in guiding their children's mathematics education during the pandemic. Our research comprises a sample of 67 participants who are parents of junior high school students with diverse occupational backgrounds in Jambi, Riau, and West Sumatra. We adopted an accidental sampling technique to select our research sample. The primary instrument for our study is a questionnaire that consists of closed questions that probe parents' emotions, knowledge, and perceptions regarding their responsibility in supporting their children's learning at home. Our survey was conducted in two phases: the initial phase spanning six months at the onset of the pandemic, and the second phase occurring several months later. Our findings indicate that during the first phase, parents were generally unaware of their roles and held negative perceptions of the online learning process. However, in the second phase, parents demonstrated a more proactive and mentoring role in supporting their children's online learning. Our study highlights the vital role of parents in facilitating their children's education during the pandemic and suggests that parental involvement is essential for optimizing online learning outcomes.